Exosomes and Extracellular Vesicles as Emerging Theranostic Platforms in Cancer Research - Giorgia Ailuno; Sara Baldassari; Francesco Lai; Tullio Florio; Gabriele Caviglioli (Cells, 2020)
Exosomes are endosome-derived nanovesicles produced by healthy as well as diseased cells. Their proteic, lipidic and nucleic acid composition is related to the cell of origin, and by vehiculating bioactive molecules they are involved in cell-to-cell signaling, both in healthy and pathologic conditions. Being nano-sized, non-toxic, biocompatible, scarcely immunogenic, and possessing targeting ability and organotropism, exosomes have been proposed as nanocarriers for their potential application in diagnosis and therapy. Among the different techniques exploited for exosome isolation, the sequential ultracentrifugation/ultrafiltration method seems to be the gold standard; alternatively, commercially available kits for exosome selective precipitation from cell culture media are frequently employed. To load a drug or a detectable agent into exosomes, endogenous or exogenous loading approaches have been developed, while surface engineering procedures, such as click chemistry, hydrophobic insertion and exosome display technology, allow for obtaining actively targeted exosomes. This review reports on diagnostic or theranostic platforms based on exosomes or exosome-mimetic vesicles, highlighting the diverse preparation, loading and surface modification methods applied, and the results achieved so far.